2023
DOI: 10.3390/antiox12020485
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol: Bridge between Antioxidant Effect, Cellular Protection, and Cognitive and Physical Performance

Abstract: The literature provides scientific evidence for the beneficial effects of cannabidiol (CBD), and these effects extend beyond epilepsy treatment (e.g., Lennox–Gastaut and Dravet syndromes), notably the influence on oxidative status, neurodegeneration, cellular protection, cognitive function, and physical performance. However, products containing CBD are not allowed to be marketed everywhere in the world, which may ultimately have a negative effect on health as a result of the uncontrolled CBD market. After the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 261 publications
1
15
0
Order By: Relevance
“…CBD, CBN, and THC were bioaccumulated and detected using liquid chromatography–tandem mass spectrometry (LC-MS/MS) in a keratinized matrix of hair and nail samples obtained by noninvasive collection from Cannabis users, with significantly higher concentrations in fingernails than in toenails and hair [ 93 ]. CBD is also known to emphasize antioxidant potential by increasing the expression of the main endogenous antioxidant system, superoxide dismutase (SOD), and glutathione peroxidase (GPx) [ 27 ]. Thus, CBD is one of the most effective protectants against UVA radiation [ 26 ], protecting keratinocytes against the effects of UVA/UVB radiation by reducing lipid peroxidation products and counteracting oxidative stress [ 46 ].…”
Section: The Topical Versus the Transdermal Route Of Administration F...mentioning
confidence: 99%
See 2 more Smart Citations
“…CBD, CBN, and THC were bioaccumulated and detected using liquid chromatography–tandem mass spectrometry (LC-MS/MS) in a keratinized matrix of hair and nail samples obtained by noninvasive collection from Cannabis users, with significantly higher concentrations in fingernails than in toenails and hair [ 93 ]. CBD is also known to emphasize antioxidant potential by increasing the expression of the main endogenous antioxidant system, superoxide dismutase (SOD), and glutathione peroxidase (GPx) [ 27 ]. Thus, CBD is one of the most effective protectants against UVA radiation [ 26 ], protecting keratinocytes against the effects of UVA/UVB radiation by reducing lipid peroxidation products and counteracting oxidative stress [ 46 ].…”
Section: The Topical Versus the Transdermal Route Of Administration F...mentioning
confidence: 99%
“…To evaluate the efficacy of pCB topical applications, a plethora of studies emphasizing the mechanisms of action at the molecular level, redox transformation, electronic structure, and stability; and the cytotoxic, phototoxic, and UVA or UVB photoprotective effects of pCBs have been performed [ 26 ]. To emphasize the mechanisms of action of pCBs at the molecular level, it has been demonstrated that CBD inhibits nuclear factor kappa B (NF-κB) and the genes involved in the expression of molecules with pro-inflammatory roles, such as cytokines and metalloproteinases [ 27 ]. Clinical studies emphasized that topical treatment with CBD-enriched ointment significantly improved skin parameters and disease symptomatology, proving that the topical application is a safe and non-invasive alternative for improving the quality of life in patients with various skin disorders [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on social media indicate that 90% of users claim they are self-medicating for diagnosable conditions such as psychiatric illness, sleep conditions, and neurological impairments [3]. There is a substantial need for evidencebased studies focusing on the epidemiology and effects of CBD use [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…There are literature reports, including the results published by us, confirming the scavenging of free radicals [ 37 , 38 , 39 ]. Recent articles present the variety of antioxidant mechanisms of cannabinoids [ 38 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%